PERAN KELOMPOK TANI PADI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA DI DESA SUNGAI MANAU KECAMATAN KUANTAN MUDIK KEBUPATEN KUANTAN SINGINGI - Handika, Aldi; ', Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT A farmers' group is a type of agricultural organization that collaborates closely with farmers to strengthen their farming operations. These farmers' groups serve as tangible and practical organizations. Some farmers' groups are also involved in other activities such as communal work, savings and loan programs, and various other efforts aimed at enhancing farming activities. In addition to their practical functions, farmers' groups also serve as educational platforms and encourage the active participation of their members. This research was conducted in Kuantan Mudik District, Kuantan Singingi Regency. This study aims (1) To determine the activities of rice farmer groups in improving the welfare of members (2) and to determine the factors that influence the role of rice farmer groups in improving welfare. This study used descriptive quantitative research methods totaling 51 people with a sample of 51 respondents sampling using census sampling techniques or taking all populations. Based on the results of the research, it can be concluded that the role of rice farmer groups in improving the welfare of members is as follows; The activities of the Rice Farmer Group ranging from the utilization of natural resources, the procurement of production facilities, and increasing the productivity of agricultural businesses showed the highest level with an average percentage of 100.0% per activity. Factors that influence the role of rice farmer groups in improving welfare can be seen from the activities of rice farmer groups, namely: utilization of available natural resources, implementation of technology recommendations, procurement of production facilities, management and marketing of results, productivity of farming, increasing environmental sustainability. Keywords: role, farmer group, social welfare